Forests for the future local strategies for forest protection, economic welfare, and social justice - Wolvekamp, Paul 1961- (London Zed Books, 1999)
"Many of the world's people depend on forests for their daily survival. This book addresses the question: how can local and indigenous communities maintain the balance between their societies and their forest environments when faced with increasing external pressures, rising populations and a growing demand for cash income and for basic needs to be met." "Given the current impasse in international forest negotiations and the inertia of most governments, it is crucially important to pay regard to and support such local citizens' initiatives. One of the things that distinguishes this book is that its authors belong to the local groups involved in these efforts. It presents their experiences and recommendations on how to re-establish community control over forest lands and preserve them for the future."--Jacket
People, politics, and forest management in Bastar: an ethnobotanical perspective / Madhu Ramnath -- Bringing the forest to the village: the creation of Chakrashila Wildlife Sanctuary in Assam / Nature's Beckon, India -- Saving the Western Ghats: blueprint solutions versus villagers' rights and responsibilities / Prakruthi, India -- Local forest management on the frontier: indigenous communities restore their forest in the Cordillera Mountains / Montanosa Research and Development Centre, Philippines -- Alternative to rainforest logging in a Chachi community in Ecuador / Accion Ecologica, Ecuador -- Protecting the last primeval forests of Paraguay: the Cordillera del Yvytyrusu and the survival of its people / Sobrevivencia, Paraguay -- Living in the Atlantic Rainforest: towards community intellectual property rights in Brazil / Vitae Civilis, Brazil -- "Washing hands with soil": restoring forest and land in Costa Rica / Arbofilia, Costa Rica -- Between logging and conservation: traditional management practices in the Cameroon rainforest / Centre pour l'Environnement et le Developpement (CED), Cameroon -- The challenge of conservation in Kahuzi-Biega National Park / Centre d'Action pour le Developpement Durable et Integre Dans les Communautes (CADIC), Democratic Republic of Congo -- Forest, water, and people: in search of a new symbiosis for Boti Falls Forest / Green Earth Organisation, Ghana -- Forests for the future: an indigenous, integrated approach to managing temperate watershed resources in Oregon / Deborah Moore, Environmental Defense Fund (EDF) and Deepak Sehgal, Confederated Tribes of Warm Springs (CTWS), USA -- Working with the woods: restoring forests and community in New Brunswick / Conservation Council of New Brunswick (CCNB), Canada --Canadian hunters fight for the forest: the Algonquins striving for territory and good management / Boyce Richardson in collaboration with Russel Diabo, Canada -- Finding common ground: adapting forest management in Krakow to the pressures of modernity / National Parks Unit, Polish Ecological Club, Poland -- Revitalising local forest management in the Netherlands: the Woodlot Owners' Association of Stramproy / ETC/Bosgroep Limburg/Both ENDS, The Netherlands -- Tigers, mushrooms, and bonanzas in the Russian Far East: the Udege's campaign for economic survival and conservation / Jenne de Beer in collaboration with Andrey Zakharenkov (Russian Far Eastern Association of the Use of Non-timber Forest Products in Khabarovsk)
Includes bibliographical references and index.
Keywords: Forests and forestry; Forest management; Forest conservation